Risks in the Drug Procurement System: Current Issues - PRODANOVA, Natalia Alekseevna (2021)
The public procurement segment is one of the components of the pharmaceutical market in Russia. Procurement of medicines and medical devices is the top sector of public procurement, both in terms of their number and the amount of contracts concluded. The procedure for concluding state contracts itself is spelled out in sufficient detail in the regulatory documents, but, despite this, risks may arise when concluding a state contract both for a potential applicant for a state order and for a state customer. The purpose of the study is to determine the possible risks when concluding a state contract of a healthcare institution for medicines and medical devices and ways to reduce them.